2013
DOI: 10.4236/ojneph.2013.33029
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dialyzer Membrane (Polyflux 210H) and Effects of Different Parameters on Dialysis Performance

Abstract: Problems frequently encountered in kidney malfunction include abnormal fluid levels in the body, increased acid levels, abnormal levels of Urea, Glucose, Endothelin, β2-Microglobulin and Complement Factor D. Parameters characterizing the structure of dialyzers are very important because they decide overall clearance of toxin molecules and at the same time should allow retaining useful molecules in the blood. In this paper, a cross sectional image of the dialyzer membrane with details of the porosity is present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 7 publications
5
22
0
Order By: Relevance
“…Figures 7 and 8 show the variation in clearance rate with dialysate flow rate. A good agreement was found between the model-predicted and Islam et al in-silico results [22]. The trend of increase in clearance with dialysate flow is also validated by comparing with the Revaclear Max dialyzer experimental (reported in Bhimani et al [25]) and Donato et al in-silico results [21].…”
Section: Effect Of Operating Conditions On Clearance Efficiencysupporting
confidence: 72%
See 2 more Smart Citations
“…Figures 7 and 8 show the variation in clearance rate with dialysate flow rate. A good agreement was found between the model-predicted and Islam et al in-silico results [22]. The trend of increase in clearance with dialysate flow is also validated by comparing with the Revaclear Max dialyzer experimental (reported in Bhimani et al [25]) and Donato et al in-silico results [21].…”
Section: Effect Of Operating Conditions On Clearance Efficiencysupporting
confidence: 72%
“…However, the model predicted values for diffusive transport of solute across the membrane are in good agreement with the Islam et al (in silico) results. In order to validate the proposed mathematical model, the model-predicted urea clearance rate was compared with Islam et al (in-silico) [22] and experimental data reported in the literature at increasing blood flow rates [23]. In Figure 4, the clearance rate of urea is compared with Polyflux 210H data provided by the manufacturer [23].…”
Section: Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…By simultaneously solving Equations (27) and (28) we correlate the transport coefficients in each membrane layer to the corresponding effective membrane coefficients, and thus, can lead to the extraction of the unknown structural quantities for each layer:…”
Section: Mass Transportmentioning
confidence: 99%
“…On the grounds that HSA cannot transport through the membrane, the pore radius should be equal to or smaller than the HSA radius. In the literature, it was found that albumin effective radius is 3.4 nm [28]; however, albumin does not have a spherical shape. The minimum radius of this protein, R min is calculated by [29]:…”
Section: Effective Properties Of the Membrane Layersmentioning
confidence: 99%